Американский претендент - Твен Марк (Библиотека П. П. Сойкина, 1998)
Экземпляры: аб. (1999) / Инвентарный номер: 41508 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Т 26 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-4